Effectiveness of Milk Supplementation on Weight and Height/Length in Stunted Toddles - Yeni Bekti Megananda; Nana Usnawati; Tutiek Herlina; Rahayu Sumaningsih; Christine Inventor Reyes (International Journal of Advanced Health Science and Technology, 2024)
Stunting or a short child was described as a toddler whose height was lower than the standard height for toddlers his age. Until now, the prevalence of stunted toddlers in Indonesia is still high. The prevalence of stunted toddlers at the Plaosan Community Health Center in the last 3 years showed an increase. The cause of stunting, apart from infection, is also related to nutritional deficiencies (micronutrients and macronutrients). The adverse effected of stunting in the short term are disruption of brain development, intelligenced, impaired physical growth, and metabolic disorders in the body. Supplementary feeded is one of the solutions in handling stunting. This study aims to determined the effectiveness of milk feeded on the weight and height/length of stunted toddlers. The typed of research used was pre-experimental with a one group pretest posttest design. The sample used a total population of 56 toddlers. The dependent variable in this studied was the weight and height/length of stunted toddlers, the independent variabled is the provision of milk for toddlers. Data collection used weight and height measurement sheets and milk feeded observation sheets. Comparative data analysis was conducted using the paired samples t test statistical test. The results of the study show that the average body weight before giving milk was 8737.5 mm and after giving milk 8923.2 mm. Body height/length before milk feeding was 804.6 mm and after milk feeding was 806.63 mm. Different test using paired samples t test obtaining the conclusion that there is a significant difference in the increase in body weight of toddlers with a significance level of 0.000 (p <0.05) and there is a significant difference in increasing the height of toddlers with a significance level of 0.000 (p <0.05). Conclution: Milk is effective to increase the weight and height/length of toddlers, so it is advisable for mothers of toddlers to get their children used to a glass of milk everyday.